Evaluación técnico financiera para un proyecto de inyección de polímeros en el bloque Río Ariari en la cuenca de los Llanos Orientales mediante simulación numérica de Yacimientos (2016)
Facing the issue of oil prices downfall due to the decline in oil demand, it is necessary to redirect research towards new improved techniques to implement sustainable processes from an environmental and economic standpoint, this to potentiate existing reserves. EOR or enhanced recovery methods it has used worldwide to extract the remaining oil in the reservoirs, after primary and secondary stage of production has come to end. The polymer solution injection in the reservoir improves sweep efficiency, reduces water mobility while increasing viscosity inducing an enhanced oil recovery. Production in the Rio Ariari Block been characterized as complicated, this due to the presence of an active aquifer, and the nature of highly viscous fluids. This work evaluates the technically and financially implementation of an injection of polymer solutions program in Rio Ariari block using the CMG STARS.